The rate of discount for evaluating public projects - Mikesell, Raymond Frech (Washington : American Enterprise Institute for Public Policy Research, 1977)
Points out the importance of the rate of discount for public policy decisions and reviews the basic issues in the debate over how that rate ought to be determined.
Includes bibliographical references: p. 55-64.
oif 08/04/2019
Loans
Keywords: Evaluation research (Social action programs); Cost effectiveness; Expenditures, Public; Externalities (Economics)